[PP.11.17] CENTRAL BLOOD PRESSURE AND ABDOMINAL AORTIC DIAMETERS: ARE THERE ANY CORRELATIONS?. (September 2016) - Grossi, A.; Tavecchia, L.; Agostinis, M.; Tandurella, N.; Pierobon, V.; Mongiardi, C.; Test, L. Robustelli; Moretti, S.; Merletti, L.; Guasti, L.; Grandi, A.M.; Maresca, A.M.
Abstract : Objective: To assess the correlation between abdominal aortic diameters and office, 24-hour and central blood pressure (BP) in untreated hypertensive patients. Design and method: We enrolled 50 patients, 35–55 years old, with mild untreated hypertension, free from cardiovascular diseases or diabetes, not smokers. We also selected 50 subjects matched for age, sex and anthropometric parameters in the control group. Each subject underwent office and 24 hours BP measurement, arterial tonometry (central BP, Pulse Wave Velocity-PWV), abdominal aortic ultrasonography (iuxtarenal and infrarenal diameters; anteroposterior-AP, laterolateral-LL) and blood-tests. Results: Abdominal aortic measures were in physiological range for all the enrolled subjects, with significant higher diameters in males. Diameters were similar between normotensive and hypertensive patients both at iuxtarenal level (longitudinal AP: 15.7 ± 1.9 mm vs 16.3 ± 1.5 mm; transversal AP: 15.7 ± 1.8 mm vs 16.3 ± 1.5 mm; transversal LL: 15.8 ± 1.7 mm vs 16.6 ± 1.7 mm, p = ns) and at infrarenal one (longitudinal AP: 14.4 ± 1.6 mm vs 14.7 ± 1.5 mm, transversal AP: 14.3 ± 1.7 mm vs 14.6 ± 1.6 mm; transversal LL: 14.3 ± 1.7 mm vs 14.7 ± 1.7 mm, p = ns). Comparing the two groups by gender, these differences were still not significant in males. Conversely, the abdominal aortic diameters were higher in hypertensives women with significant difference at iuxtarenal (p = 0.005) and infrarenal level (p = 0.05). No significant correlations were found between office, central and 24-hour BP and aortic diameters for the whole popolation, whereas there was a mild correlation in females between iuxtarenal aortic diameters and systolic (r = 0.327, p = 0.019) and diastolic (r = 0.335, p = 0.016) central BP. Moreover, PWV correlated with iuxtarenal diameters in the whole population (r = 0.394, p < 0.001), in hypertensives (r = 0.403, p < 0.001) as well as in normotensives (r = 0.352, p < 0.001). Finally, both iuxtarenal and infrarenal aortic diameters correlated with age, abdominal circumference, BMI and serum uric acid. Conclusions: The hypertension contribution to abdominal aortic dilation appeared significant only in females, suggesting the role of a different hormonal pattern. We also found different iuxtarenal and infrarenal aortic remodelling, most likely due to different vascular wall structure.